La peculiare costituzione dell'Unione Europea - Fossum, John Erik (Studi e saggi, 2012)
A unique political animal, the European Union has given rise to important constitutional conundrums and paradoxes that John Erik Fossum and Agustín José Menéndez explore in detail in this book. The authors consider the process of forging the EU's constitution and the set of fundamental norms that define the institutional structure, the decision-making procedures, and the foundations of the Union's democratic legitimacy. Their analysis illuminates the distinctive features of the EU's pluralist constitutional construct but also the interesting parallels to the Canadian constitutional experience and provides the tools to understand the Union's development, especially during the Laeken (2001-2005) and Lisbon (2007-2009) processes of constitutional reform.